Amyloid-clearing proteins and their epigenetic regulation as a therapeutic target in Alzheimer’s disease - Nalivaeva, Natalia N.; Belyaev, Nikolai D.; Kerridge, Caroline; Turner, Anthony J. (Frontiers in Aging Neuroscience, 2014)
Abnormal elevation of amyloid β-peptide (Aβ) levels in the brain is the primary trigger for neuronal cell death specific to Alzheimer’s disease (AD). It is now evident that Aβ levels in the brain are manipulable due to a dynamic equilibrium between its production from the amyloid precursor protein (APP) and removal by amyloid clearance proteins. Clearance can be either enzymic or non-enzymic (binding/transport proteins). Intriguingly several of the main amyloid-degrading enzymes (ADEs) are members of the M13 peptidase family (neprilysin (NEP), NEP2 and the endothelin converting enzymes (ECE-1 and -2). A distinct metallopeptidase, insulin-degrading enzyme (IDE), also contributes to Aβ degradation in the brain. The ADE family currently embraces more than 20 members, both membrane-bound and soluble, and of differing cellular locations. NEP plays an important role in brain function terminating neuropeptide signals. Its decrease in specific brain areas with age or after hypoxia, ischaemia or stroke contribute significantly to the development of AD pathology. The recently discovered mechanism of epigenetic regulation of NEP (and other genes) by the APP intracellular domain (AICD) and its dependence on the cell type and APP isoform expression suggest possibilities for selective manipulation of NEP gene expression in neuronal cells. We have also observed that another amyloid-clearing protein, namely transthyretin (TTR), is also regulated in the neuronal cell by a mechanism similar to NEP. Dependence of amyloid clearance proteins on histone deacetylases and the ability of HDAC inhibitors to up-regulate their expression in the brain opens new avenues for developing preventive strategies in AD.